Formulasi dan Evaluasi Fisik Sediaan Salep Dari Ektrak Bonggol Pisang Kepok (Musa paradisiaca L) - Mubarok, Azis Zamzam; Wahyuni, Nency; Wardani, Diah (Jurnal Medika Farmaka, 2024)
Wounds are a condition that is often experienced by everyone, whether with mild, moderate or severe severity, injury is the loss or destruction of body tissue. The wound healing process occurs in damaged tissue which is divided into three phases, namely the inflammatory phase, the proliferative phase and the maturation phase, which is tissue remodeling. Research on kepok bananas shows that banana weevil extract has higher antimicrobial activity than its midrib extract. In addition to accelerating wound healing, banana weevil can help repair damaged skin structures without scars and increase the revitalization of epidermal tissue, formation of fibroblasts and infiltration of inflammatory cells in the wound area. can be developed into cosmetics. this is the reason for making an ointment containing banana weevil extract with formulation 1 containing 1 g ethanol, formulation 2 containing 1.5 g ethanol, and formulation 3 containing 2 g ethanol. By evaluating the preparations to determine the physical stability of the preparations made including organoleptic testing, homogeneity testing, pH testing, testing the dispersion of the preparation and testing the organoleptic stability of the preparation, the pH stability of the preparation. The results showed that in the organoleptic test only 2 formulations met the quality standards, in the homogeneity test there were 2 formulations that met the criteria, in the pH test all formulations met the quality standards, in the dispersion test all formulations met the criteria, and in the stability test there were differences in storage. under exposure to sunlight but there is no change in the stability of the pH of the preparation made. Based on the research that has been done, it can be concluded that all formulations and physical evaluations of ointment preparations from the Kepok Banana Weevil Extract (Musa paradisiaca L). with variations of kepok banana weevil extract at F1 (15%), F2 (20%), and F3 (25%) met the requirements of good organoleptic, pH (4-7), and viscosity (2000-5000 mPas) tests.